Process / industrial instruments and controls handbook, sixth edition - McMillan, Gregory K.; Vegas, P. Hunter (McGraw-Hill Education, 2019)
Extensive and practical plant-based knowledge to achieve the best automation system. This fully updated on-the-job reference contains all the automation and control information you need to make timely decisions and maximize process capacity and efficiency. Featuring contributions from 50 top technical experts, Process/Industrial Instruments and Controls Handbook, Sixth Edition, covers the latest technologies and advances. More importantly, the book helps you select the right instrumentation, install and maintain it correctly, and leverage it to maximize plant performance and profitability. You will get all you need to know to execute a successful automation project including time-saving tables, lists of essential best practices, and hundreds of topic-defining illustrations.